Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/cid/ciz1009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Community-Based Nutritional Interventions on Children of Women Living With Human Immunodeficiency Virus in Rural India: A 2 × 2 Factorial Intervention Trial

Abstract: Background Malnutrition is a common clinical concern among children in low-income communities affected by human immunodeficiency virus (HIV). We examined the effect of a community-based nutritional intervention on anthropometric and clinical outcomes of children of women living with HIV in rural India. Methods We assigned women living with HIV and their child (oldest 3–8 years) to 1 of 4 programs: (1) community-based HIV care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Penelitian yang dilakukan Shin et al,(2020) yang diadakan di pedesaan India. Penelitian ini merekrut peserta dari pusat layanan kesehatan primer puskesmas.…”
Section: A Ceramah Dan Bermain Peranunclassified
“…Penelitian yang dilakukan Shin et al,(2020) yang diadakan di pedesaan India. Penelitian ini merekrut peserta dari pusat layanan kesehatan primer puskesmas.…”
Section: A Ceramah Dan Bermain Peranunclassified
“…Han et al [ 13 ] showed that patients with hepatitis C virus (HCV) infection had defective T cell function, and the direct effect of antiviral therapy improved the proliferation of HCV-specific CD8+ T cells. In a study by Shin et al [ 14 ], providing nutritional education and food supplements to human immunodeficiency virus- (HIV-) infected women significantly increased weight and CD4+ T cells, and these interventions can be integrated into HIV care programs in low-income areas. Schlosse et al [ 15 ] inoculated C57BL/6 mice, BALB/C nude mice, Wistar rats, and European rabbits with wild boar-derived HEV-3 strain, and monitored the replication and shedding of the virus and the humoral immune response to it.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition problems associated with HIV and its treatment occur in most patients and could be indicative of the stage and progression of the infection. Research suggested that proper nutrition care is necessary to strengthen the immune system, delay the disease progression, and improve patients' quality of life [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%